Analisis Tingkat Kesehatan PT. Bank Perkreditan Rakyat Serang (Perseroda) Dengan Menggunakan Metode RGEC - Shavab, Firli Agusetiawan (Tirtayasa Ekonomika, 2024)
This study analyzes the health level of PT. Bank Perkreditan Rakyat (BPR) Serang (Perseroda) using the RGEC method for the period of 2019-2022. The analysis results indicate that the financial health of PT. BPR Serang fluctuates across various aspects. The Risk Profile highlights challenges in managing credit and liquidity risks, especially during the COVID-19 pandemic. Good Corporate Governance (GCG) is rated very well with a composite score of 143. The Earnings analysis through Return on Assets (ROA) shows fluctuating asset usage efficiency but mostly remains in the "Very Healthy" and "Healthy" categories. Capital exhibits a gradual decline but remains within the "Very Healthy" to "Healthy" categories. Recommendations are provided to improve risk management, operational efficiency, capital strengthening, and the application of GCG principles. This study is expected to contribute to understanding the factors influencing bank health and serve as a reference for policymakers in the banking sector.